PERJANJIAN NOMINEE DALAM KEPEMILIKAN TANAH OLEH WARGA NEGARA ASING DI BALI (STUDI KASUS DI KABUPATEN BADUNG) - , Anjarini Kencahyati ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Research on the nominee agreement in the ownership of land by foreigner in Bali (a case study in Badung District) aims to determine the legal impact toward nominee agreement when the nominee is not known their existences and the form of settlement when dispute arise between the parties bound by a nominee agreement. This research is an empirical-juridical approach research that is based on field research, and to complete data obtained from field research, library research is conducted. Data that are obtained from both library research and field research will be analyzed with descriptive-qualitative method, the method of data analysis by classifying and selecting the data obtained from field research according to the quality and veracity, connected with theories derived from literature study, so the answer of the problems posed is obtained. The research result shows that the Right of Use shall be deemed less profitable for the foreigners so that the implementation of various regulations on the Right of Use in Bali especially in Badung District do not run well, so they use nominee agreement in the ownership of land in Bali.With the agreement nominee, the foreigners just borrow the identity of an Indonesian citizen who lives in Bali to include his name in a certificate of land and foreign citizens considered that the agreement is far more practical and beneficial to both parties. Technically, the author analyze several problems that will arise if the land is transferred while the nominee dies, disappears, or unknown his address. But, these problems have been anticipated by the foreigner concerned by making an nominee agreement, which is agreed as follows: 1. The statement that the land was purchased with money from foreign accounts and nominee is only borrowed his name to be used in the name of the certificate. Any costs arising from the purchase of the land is borne by foreigners (such as tax expenses /, building permits). 2. An a rent agreement is created between the foreigner and the nominee without the limit of the time and with the engineered rentâs fee, so as if it is legal and not against the rules. 3. absolute power of attorney is made from the Indonesian citizen (nominee) to foreigners who may sell and lease it to anyone and such power of attorney can not be revoked anymore. 4. The nominee agreement is binding on all heirs of both parties between foreigners and nominee.